2019
DOI: 10.32479/ijeep.8367
|View full text |Cite
|
Sign up to set email alerts
|

Energy Risk Management and Cost of Economic Production Biodiesel Project

Abstract: Although electricity in Thailand is still sufficient to provide services, but there may be a risk in future from relying solely only on oil energy. Therefore, alternative energy is a good way to distribute fuel. The growth rate of community brings higher levels of imported energy from foreign countries including expansion of large projects resulting in opening of exploration and production rights for petroleum to increase energy security and reduce domestic risks. This research aims study of economic productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, financing energy efficiency management projects can be a real challenge, and the energy costs are a significant part of the organization's total operating costs [57]. Cost reduction and efficiency improvement are critical objectives for the organizational performance.…”
Section: Project Management In An Efficient Energy Consumptionmentioning
confidence: 99%
“…However, financing energy efficiency management projects can be a real challenge, and the energy costs are a significant part of the organization's total operating costs [57]. Cost reduction and efficiency improvement are critical objectives for the organizational performance.…”
Section: Project Management In An Efficient Energy Consumptionmentioning
confidence: 99%
“…The economic analysis of biodiesel synthesis showed that raw materials and utilities covered 86 % of the total operating cost. Moreover, the mass balance is used as a reference to determine the quantity of raw material required to meet the necessary production capacity [144]. Similarly, the consumption of utilities is based on the type of process applied.…”
Section: Operating Costmentioning
confidence: 99%
“…These studies have focused on various dimensions including economic, energy, environmental, social and technical. For example, a number of studies have assessed the economic impacts of palm oil-based biofuel in terms of subsidy, tax and prices of biodiesel, cost of economic production for biodiesel project, and life cycle cost of biodiesel, for example, Laung-Iem and Thanarak (2021), Chantawong et al (2020), Romprasert and Jermsittiparsert (2019) and Siralertruksa et al (2012a). Several studies have assessed the energy impacts of palm oil-based biofuel, for example, Nutongkaew et al (2019), Prueksakorn et al (2010), Pleanjai and Gheewala (2009) Prueksakorn and Gheewala (2008) and Keson et al (2015) have focused specifically on resource potential assessment of palm oil-based biofuel production.…”
Section: Introductionmentioning
confidence: 99%